Climate change-induced shifts in the ecological niches of Parkia biglobosa (Jacq.) and Vitellaria paradoxa CF Gaertn, two species of agroforestry parks in Benin, West Africa - Chaffra Charles Yabi; Jacques Idohou Kadjogbé Ayena; Séverin Biaou; Serge Adomou; Thierry Dèhouégnon Houehanou; Gérard Nounagnon Gouwakinnou (Trees, Forests and People)
Understanding the effects of climate change on species distribution patterns is fundamental to biogeography and evolutionary ecology, especiallyfor socio-economically important agroforestry species such as Parkia biglobosa R.Br. ex Benth and Vitellaria paradoxa CF Gaertn. However, gaps remain regarding the evolution of ecological niches of these widespread species. This study examines the effects of climate change on P. biglobosa and V. paradoxa, two key species of agroforestry parklands in Benin. By integrating intraspecific variation into niche modeling, three homogeneous subgroups (North, Center, and South) were identified and analyzed under current and future climate conditions. Maximum Entropy Modeling (MaxEnt), was used, chosen for its predictive power and flexibility in correcting for data bias. Climate projections were based on common socio-economic scenarios (SSP2-4.5 and SSP5-8.5), representing a moderate mitigation scenario and a high emissions scenario, respectively. The results showed significant climate change effects across subgroups for both species, mediated by temperature and humidity. Under the SSP2-4.5 scenario, the northern subgroup of P. biglobosa exhibited habitat shifts towards the central and southern subgroup regions, while the central and southern subgroups showed predictive habitat loss. For V. paradoxa, this scenario predicted significant habitat loss for the northern and central subgroups, while the southern subgroup demonstrated habitat expansion along altitudinal gradients. The more severe SSP-5–8.5 scenario predicted extensive habitat loss for both species. The Sudano-Guinean and Guineo-Congo zones remain climatically suitable for both species under future projections. The most pronounced interspecific niche overlap occurred between the northern and southern subgroups, indicating considerable ecological similarity. These results highlight the need for climate-adaptive management strategies in agroforestry systems with particular emphasis on subgroups facing imminent habitat loss. Future research directions should explore adaptive management approaches while maintaining essential ecosystem services and supporting local livelihoods.